2021
DOI: 10.1016/j.scitotenv.2020.142298
|View full text |Cite
|
Sign up to set email alerts
|

Sources and routes of SARS-CoV-2 transmission in water systems in Africa: Are there any sustainable remedies?

Abstract: Governments across the globe are currently besieged with the novel coronavirus (COVID-19) pandemic caused by SARS-CoV-2. Although some countries have been largely affected by this pandemic, others are only slightly affected. In this regard, every government is taking precautionary measures to mitigate the adverse effects of COVID-19. SARS-CoV-2 has been detected in wastewater raising an alarm for Africa due to the poor water, sanitation, and hygiene (WASH) facilities. Also, most countries in Africa do not have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 74 publications
0
34
0
Order By: Relevance
“…Thus, the variants of SARS-CoV-2 further challenged the campaign against the COVID-19 pandemic. Studies have shown that close contact and respiratory droplets can't explain all infections ( Tabatabaeizadeh, 2021 ), and the environmental transmissions have become an important mechanism of COVID-19 spread, such as water ( Sunkari et al, 2021 ), aerosol ( Santarpia et al, 2020 ), and low-temperature enhanced spread ‘cold chain’ ( Zhang, 2020 ). Among these, aerosol transmission is relatively difficult to prevent.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the variants of SARS-CoV-2 further challenged the campaign against the COVID-19 pandemic. Studies have shown that close contact and respiratory droplets can't explain all infections ( Tabatabaeizadeh, 2021 ), and the environmental transmissions have become an important mechanism of COVID-19 spread, such as water ( Sunkari et al, 2021 ), aerosol ( Santarpia et al, 2020 ), and low-temperature enhanced spread ‘cold chain’ ( Zhang, 2020 ). Among these, aerosol transmission is relatively difficult to prevent.…”
Section: Introductionmentioning
confidence: 99%
“…In lower-resource settings, as sub-Saharan Africa, Indonesia and India, a significant part of the population is not connected to sewers and uses pit toilets, septic tanks or still practices open defecation [ 29 , 76 , 77 , 78 , 79 ]. Waterways are also used as open sewers and the discharge of untreated wastewater into the environment is an usual practice [ 77 , 78 ]. In these contexts, testing of surface water contaminated by sewage could be used as an alternative for viral monitoring [ 29 , 35 , 80 ].…”
Section: Sars-cov-2 Rna Detection In Surface Watermentioning
confidence: 99%
“…As reported, there has been accumulating evidence of a fecally-mediated route of transmission of SARS-CoV-2 [3]. This rapidly evolving pandemic urgently demands that the scientific community analyzes and evaluates the potential unknown sources of virus transmission that may contribute to Covid-19's resurgence, as well as effective approaches to mitigate its spread through the already known pathways [4].…”
Section: Perspectivementioning
confidence: 99%